Playing in the Gif(t) Economy. (November 2014) - Uhlin, Graig
This article examines the creation and circulation of graphics interchange format (GIF) animations as a mode of play with moving images. It understands the production and sharing of GIFs as part of a gift economy, as opposed to commodity exchange, where the liberation of the image from its original source entails a ludic appropriation that directs focus to the often-overlooked detail, gesture, or action. GIFs open an inquiry about the divide between art and commerce, as well as between play and work. They entail a type of spectatorship that revives outmoded forms of viewership, recalling the animistic tendencies of the reception of early cinema, and privileges the unauthorized and playful sharing of moving images through the figure of what this essay calls the "dispossessive spectator."